Exploring brain changes of impulse control disorders in Parkinson's disease: An ALE study - Gu, Lihua; Shu, Hao; Wang, Yanjuan; Xu, Hui (Frontiers in Aging Neuroscience, 2022)
Background: Previous neuroimaging studies reported inconsistent results for comparison between Parkinson’s disease with impulse control disorder (PD-ICD) and without ICD (PD-no ICD). Methods: A search was performed in databases (PubMed and Web of Science) to identify studies published before May 2022. An anatomic likelihood estimation (ALE) method study was made for neuroimaging studies in PD-ICD. Results: The study included 20 studies (including 341 PD-ICD and 437 PD-no ICD). PD-ICD patients showed significant cortical thinning in the right inferior frontal gyrus (IFG), the right middle frontal gyrus (MFG), the left superior frontal gyrus (SFG), the right precentral gyrus (PCG) and the left cingulate gyrus (CG), compared to PD-no ICD patients. The ALE study showed reduced resting-state brain activation in the right IFG, the right PCG, the left insula and the right transverse temporal gyrus (TTG) in PD-ICD, compared to PD-no ICD patients. In addition, PD-ICD showed increased resting-state brain activation in the right caudate, the bilateral insula and the left orbital gyrus (OG), compared to PD-no ICD patients. The study indicated reduced task-related brain activation in the right caudate, the right MFG, the right lentiform nucleus (LN) and the right precuneus (PCUN) in PD-ICD, compared to PD-no ICD patients. The study showed increased task-related brain activation in the left inferior parietal lobule (IPL), the right medial frontal gyrus, the right caudate and the right PCG in PD-ICD, compared to PD-no ICD patients. Conclusions: The present ALE analysis has confirmed that brain changes in frontal, temporal and basal ganglia regions are among the most frequently reported in PD-ICD. Deficits in these regions could play a role in diagnosis of PD-ICD.